Protein acylation by saturated very long chain fatty acids and endocytosis are involved in necroptosis. Issue 9 (16th September 2021) - Pradhan, Apoorva J.; Lu, Daniel; Parisi, Laura R.; Shen, Shichen; Berhane, Ilyas A.; Galster, Samuel L.; Bynum, Kiana; Monje-Galvan, Viviana; Gokcumen, Omer; Chemler, Sherry R.; Qu, Jun; Kay, Jason G.; et al.
Summary: Necroptosis is a form of cell death characterized by receptor-interacting protein kinase activity and plasma membrane permeabilization via mixed-lineage kinase-like protein (MLKL). This permeabilization is responsible for the inflammatory properties of necroptosis. We previously showed that very long chain fatty acids (VLCFAs) are functionally involved in necroptosis, potentially through protein fatty acylation. Here, we define the scope of protein acylation by saturated VLCFAs during necroptosis. We show that MLKL and phosphoMLKL, key for membrane permeabilization, are exclusively acylated during necroptosis. Reducing the levels of VLCFAs decreases their membrane recruitment, suggesting that acylation by VLCFAs contributes to their membrane localization. Acylation of phosphoMLKL occurs downstream of phosphorylation and oligomerization and appears to be, in part, mediated by ZDHHC5 (a palmitoyl transferase). We also show that disruption of endosomal trafficking increases cell viability during necroptosis, possibly by preventing recruitment, or removal, of phosphoMLKL from the plasma membrane. Graphical abstract: Highlights: Saturated VLCFAs are differentially incorporated into proteins during necroptosis pMLKL/MLKL exhibit acylation by VLCFAs in necroptosis pMLKL/MLKL acylation is, in part, mediated by ZDHHC5 Perturbing trafficking to the plasma membrane rescues cell death during necroptosis Abstract : Pradhan et al. show that MLKL and pMLKL are acylated by saturated very long chain fatty acids during necroptosis and that the disruption of endocytosis decreases the levels of membrane-bound pMLKL and MLKL, resulting in a rescue from cell death during this process.